Avaliando dois programas de pesquisa sobre a teoria dos modelos Relacionais - Pauly, Daniel Uptmoor (Universidade do Vale do Rio dos Sinos, 2017)
The main goal of this dissertation is to study the theory about human sociability according to Fiske. The specific goal of this dissertation is to compare two rival research programs that describe the social cognition as defended by Fiske. Two different explanations about the Relational Models Theory from Fiske are presented by two rival research programs. The first, defended by Bolender, incorporates fields from physics, biology, philosophy of language and states that, being the four measurement scales fundamental to the four elementary forms of sociality, it is possible that they have its base on a central pattern generator. The second, defended by Favre and Sornette, utilizes math and logic to show how the four elementary forms of sociality appear and does not mention the four measurement scales. We will apply philosophical metatheories to evaluate both research programs. The importance of evaluating both programs consists in an effort towards deepening the understanding of the Relational Models Theory.
Keywords: Modelos relacionais; Fiske; Escalas de medida; ACCNPQ::Ciências Humanas::Filosofia